2015
DOI: 10.2147/ijn.s86238
|View full text |Cite
|
Sign up to set email alerts
|

Para amino benzoic acid-derived self-assembled biocompatible nanoparticles for efficient delivery of siRNA

Abstract: A number of diseases can result from abnormal gene expression. One of the approaches for treating such diseases is gene therapy to inhibit expression of a particular gene in a specific cell population by RNA interference. Use of efficient delivery vehicles increases the safety and success of gene therapy. Here we report the development of functionalized biocompatible fluorescent nanoparticles from para amino benzoic acid nanoparticles for efficient delivery of short interfering RNA (siRNA). These nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Several materials including polymeric micelles7, dendrimers8, various nanoparticles9 and liposomes10 are being used in drug delivery systems. Research over a period of time has shown the delivery of small molecule therapeutics and its subsequent release in response to external stimuli such as temperature, light1112, redox reagents13, ultrasound10, pH, enzymes, etc.…”
mentioning
confidence: 99%
“…Several materials including polymeric micelles7, dendrimers8, various nanoparticles9 and liposomes10 are being used in drug delivery systems. Research over a period of time has shown the delivery of small molecule therapeutics and its subsequent release in response to external stimuli such as temperature, light1112, redox reagents13, ultrasound10, pH, enzymes, etc.…”
mentioning
confidence: 99%